On the design of some devices for localization and extinguishing wildfires of different intensities; Вестник Карагандинского университета. Серия Физика; № 1 (97) - Kasymov D. P. Denis Petrovich (2020, 2020)
Topicality of the study of natural fires and techniques to control them is obvious. About 18 000 people in theRussian Federation lose annually their lives as a result of forest fires. Analysis is shown that forest fires areparticularly frequent in Siberia and the Far East of Russia, where the number of deaths from forest fires up to10 000 people exceeds the same indicator in the European part of Russia by 4–5 times. General situation inthe world shows shortcomings in the existing system of monitoring forests and the low efficiency of themethods used to localize and extinguish fires. Development of devices for localizing and extinguishing wildfires of various intensities is considered, based on knowledge of flame structure, including drying, heating,pyrolysis and mixing with atmospheric oxygen zones, which can be affected by relatively low energy disturbances (shock waves) minimizing environment damage. Theoretical and experimental studies show that shockwaves lead to increasing pressure in them at the time of interaction with unstable zones, which increases thesuppression efficiency further. It is shown that the practical use of considered technological solutions willmake it possible to increase the effectiveness and efficiency of measures to suppress wildfires